What Determines Long-Run Macroeconomic Stability? : Democratic Institutions - Subramanian, Arvind (IMF Working Papers; Working Paper ;, 2004)
We examine the deep determinants of long-run macroeconomic stability in a cross-country framework. We find that conflict, openness, and democratic political institutions have a strong and statistically significant causal impact on macroeconomic stability. Surprisingly the most robust relationship of the three is for democratic institutions. A one standard deviation increase in democracy can reduce nominal instability nearly fourfold. This impact is robust to alternative measures of democracy, samples, covariates, and definitions of conflict. It is particularly noteworthy that a variety of nominal pathologies discussed in the recent macroeconomic literature, such as procyclical policy, original sin, and debt intolerance, have common origins in weak democratic institutions. We also find evidence that democratic institutions both strongly influence monetary policy and have a strong, independent positive effect on stability after controlling for various policy variables.